Unexpected side effects in biocrust after treating non‐native plants using carbon addition. (19th January 2020) - Chiquoine, Lindsay P.; Abella, Scott R.; Greenwood, Joshua L.; DeCorte, Adria
Abstract : Carbon addition has been proposed as an alternative to herbicide and manual removal methods to treat non‐native plants and reduce non‐target effects of treatments (e.g. impacts on native plants; surface disturbance). On Mojave Desert pavement and biocrust substrates after experimental soil disturbance and carbon addition (1, 263 g C/m 2 as sucrose), we observed declines in lichens and moss cover in sucrose‐treated plots. To further explore this unforeseen potential side effect of using carbon addition as a non‐native plant treatment, we conducted biocrust surveys 5 and 7 years after treatments, sampled surface soils to observe if treatments additionally affected soil filamentous cyanobacteria, and conducted laboratory trials testing the effects of different levels of sucrose on cyanobacteria and desert mosses. Sucrose addition to biocrust plots reduced lichen and moss cover by 33–78% and species richness by 40–80%. Sucrose reduced biocrust cover in biocrust plots to levels similarly detected in pavement plots (<1%). While cyanobacteria in the field did not appear to be affected by sucrose, laboratory tests showed negative effects of sucrose on both cyanobacteria and mosses. Cyanobacteria declined by 41% 1 month after exposure to 5.4 g C/m 2 equivalent solutions. We detected injury to photosynthesis in mosses after 96 hour exposure to 79–316 g C/m 2 equivalent solutions. Caution is warranted when using carbon addition, at least in the form and concentration of sucrose, as a treatment for reducing non‐native plants on sites where conserving biocrust is a goal.